ìSPEAK: Using Mobile-Based Online Learning Course to Learn ‘English for the Workplace’ - M. Rafiq, Karmila Rafiqah; Hashim, Harwati; Md Yunus, Melor; Norman, Helmi (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Due to the rise of the digital era, various industries demand employees with a proficient communicative English skills, but many are still not up to par with the demands. One solution for this is to provide communicative English trainings for employees, especially support staffs, yet face-to-face trainings have many limitations, which can be overcome through mobile learning. Due to the fact that mobile learning can be accessed anytime and anywhere by anyone, the Massive Online Open Courses (MOOC) is one of the platforms that can be used to curb the issue. This paper aimed to identify the perceptions of support staffs towards using ‘ìSPEAK: English for the Workplace’ in MOOC. A total of 30 respondents were selected through purposive sampling and a survey through a 4-point Likert scale questionnaire was given out. The main findings showed that overall, the support staffs have a positive attitude towards using ìSPEAK. Nevertheless, half of them were unsure of the reliability of the sources available in the course. However, the findings of this study implied that ìSPEAK could be one of the training alternatives for support staffs to improve and increase their communicative ability. Future research can look into designing and developing various modules of communicative English in various mobile learning platforms, which could cater to different levels of proficiency of learners.